You are not logged in.

Go back

No, it's right. It's just that I wouldn't have thought that such a complicated expression could be simplified into such a simple one like that.

what do you mean? is it not right

How very elegant and unexpected.

Sinx*Sin2x + Cosx*Cos2x= Sinx[Sin(x+x)] + Cosx[(Cos(x+x)]= Sinx[2SinxCosx]+ Cosx[Cos²x - Sin²x]Rearranging the terms,= Cosx[2Sin²x + Cos²x - Sin²x]= Cosx[Sin²x + Cos²x]=Cosx (since Sin²x + Cos²x=1).

Hi,How would I solve this question:express sinx sin(2x) + cosx cos(2x) in terms of cosxI am really stuck in this.Danny